Defense Strategy of Wakatobi Language Sikka Island in the Tourism Destination Area (A Sociolinguistic Study) - Abdul Hamid; Idris Mboka (Budapest International Research and Critics University, 2023)
Language defense can be realized if the spoken community continues to use that language in the realm of communication, even though there is a realm of using other languages in the interaction of multilingual communities. This study aims to describe the strategy for maintaining the Wakatobi language in the Sikka Archipelago in the Kojadoi Tourism Destination Area. This research method is a qualitative descriptive method. The research data was collected using observation, interview, documentation, and questionnaire methods. The data analysis technique in this research is discourse analysis technique. Based on research data regarding the strategy for maintaining the Wakatobi Language in the Kojadoi Tourism Destination Area, it can be argued that the strategy for maintaining the Wakatobi Language in the Kojadoi Tourism Destination Area includes: 1) Intensification of the function of language as an inter-ethnic communication tool, 2) Integration of Language and Culture, 3) Government Program and Service Policies, 4) Use of language in various domains of communication.